A REVIEW ON VARIOUS MULTIMODAL BIOMETRIC TECHNIQUES - Navjeet Kaur (International Journal of Research Science and Management, 2015)
The best way to check the authenticity of the user is to use their body characteristics as a password such as face, voice,iris,fingerprint,palmprint etc. this makes the system more secured as every human being has different human traits. This paper gives a review on different biometric authentication patterns. The use of multimodal features gives more effective result than a unimodal techniques and hence makes the system more secure and effective.